THE CORRELATION BETWEEN THE FREQUENCY OF WATCHING ENGLISH MOVIES AND VOCABULARY MASTERY OF THE FOURTH-SEMESTER STUDENTS OF THE ENGLISH STUDY PROGRAM OF FKIP OF UNIVERSITAS RIAU - Puji Kardela; Afrianto Daud; Maria Safriyanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research aimed to find out whether there was a significant correlation between the frequency of watching English movies and vocabulary mastery of the fourth-semester students of the English study program of FKIP of Universitas Riau. The sample of this research consisted of 35 students selected by random sampling technique. The instruments of the research were a questionnaire and a vocabulary test. The data were collected through a questionnaire to know the frequency of watching English movies and a test to measure students’ vocabulary mastery. The test was used to assess students’ vocabulary mastery.The research findings showed that the frequency of watching English movies of the fourth-semester students of FKIP of Universitas Riau is categorized into average level. The vocabulary mastery of the fourth-semester students of FKIP of Universitas Riau is categorized into mediocre level. Pearson Product Moment Correlation method was used to correlate both the frequency of watching English movies (X) and vocabulary mastery (Y). The result showed that there was a significant correlation (0.694) between the frequency of watching English movies and students’ vocabulary mastery. It can be concluded that there is a significant correlation between the frequency of watching English movies and vocabulary mastery of the fourth-semester students of the English study program of FKIP of Universitas Riau.Key Words: Correlation, English Movies, Vocabulary Mastery.